Analisis Yuridis Penetapan Anak Dengan Status Kewarganegaraan Ganda Ditinjau Dari Hukum Perdata Internasional (Studi Kasus Penetapan Nomor 703/Pdt.P/2019/PN.Jkt.Utr) - Permatasari, Deshy Eka; Laurenza, Dias Prima; Zahra, Lintang Aulia; Azzahra, Natasya Fhadyah; Zahia, Reyna (Media Hukum Indonesia (MHI), 2024)
In the era of globalization, the increasing number of mixed marriages between Indonesian citizens (WNI) and foreign citizens (WNA) is becoming an increasingly common phenomenon. These marriages often produce children who have the potential to have dual citizenship, which poses significant challenges in terms of civil rights, access to education, inheritance rights, and other legal obligations. Indonesia has regulated this issue through Law Number 12 of 2006 concerning Citizenship of the Republic of Indonesia, which allows children resulting from mixed marriages to have dual citizenship up to a certain age. This research uses a normative juridical approach and a case approach to analyze the application of international private law to the determination of dual citizenship status for children resulting from mixed marriages. Case study of Determination Number 703/Pdt.P/2019/PN. Jkt. Utr is used to describe the implementation of the rule. The research results show that even though regulations exist, their implementation faces various obstacles, both from administrative and legal aspects. In addition, this research identifies the importance of strengthening international cooperation, empowering consumers, and developing innovation in the online lending industry to increase financial access and consumer protection. Continuous evaluation of regulatory effectiveness is also critical to ensure that regulations remain relevant and responsive to technological developments and changing business practices.